Strobe double phase estimator: a multipath mitigating technique for BOC signal in GNSS based on double phase estimator. (16th May 2016) - Chengtao, Xu; Zhe, Liu; Xiaomei, Tang; Feixue, Wang
Summary: Double phase estimator (DPE) is an unambiguous binary offset carrier (BOC) tracking algorithm for band‐limited receivers in Global Navigation Satellite Systems. Based on the strobe pulse method, the DPE was modified by introducing a strobe waveform in the prompt signal correlation process of the subcarrier phase lock loop in this paper.. This strobe DPE (SDPE) employs no additional correlators. Two different reference strobe waveforms and their receiving structures are provided. The performance of the SDPE is characterized according to the subcarrier multipath error envelope (SMEE) and the tracking jitter. Simulation results show that, relative to conventional DPE, the first waveform employed in this study provides a reduction in the SMEE area of 81.1% and 75.1% for BOC(1, 1) and BOC(14, 2) signal, respectively. The second waveform employed in this study provides a reduction in the SMEE area of 82.5% and 76.8% for BOC(1, 1) and BOC(14, 2) signal, respectively. They also both outperform the double estimator about 64.4% and 53.2% for BOC(1, 1) and BOC(14, 2) signal in the SMEE area. However, the SDPE experiences a loss of −6 and −7.25 dB, respectively, for two reference waveforms in terms of the post‐coherent signal‐to‐noise ratio, which impacts its tracking precision. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, a strobe double phase estimator technique is proposed with two reference strobe waveforms based on the strobe pulse method. The SDPE algorithm has a better performance with 75.1% to 82.5% than the conventional DPE for different BOC signals. However, the SDPE experiences a loss of ‐6 and ‐7.25 dB, respectively, in terms of the post‐coherent signal‐to‐noise ratio